2022
DOI: 10.3390/f13071045
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Wood Particleboard Drilling Operating Parameters by Means of the Artificial Neural Network Modeling Technique and Response Surface Methodology

Abstract: Drilling is one of the oldest and most important methods of processing wood and wood-based materials. Knowing the optimum value of factors that affect the drilling process could lead both to high-quality furniture and low-energy consumption during the manufacturing process. In this work, the artificial neural network modeling technique and response surface methodology were employed to reveal the optimum value of selected factors, namely, drill tip angle, tooth bite, and drill type of the delamination factor at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
10
6
1
Order By: Relevance
“…Based on the obtained performance indicators during the training, testing, and validation phase, it could be concluded that the developed ANN models are able to predict adequately the dependent variables. Compare these results with the results presented in the literature [14], in which the same methodology was applied in the case of prelaminated particleboards drilling, one could observe that the overall performance of the developed artificial neural networks for the MDF boards is slightly better than the performance of the ANN models, which were designed for particleboards (Table 6). This could be due to the fact that the MFD have more of a homogenous structure than the prelaminated wood particleboards.…”
Section: Ann Modelingsupporting
confidence: 66%
See 3 more Smart Citations
“…Based on the obtained performance indicators during the training, testing, and validation phase, it could be concluded that the developed ANN models are able to predict adequately the dependent variables. Compare these results with the results presented in the literature [14], in which the same methodology was applied in the case of prelaminated particleboards drilling, one could observe that the overall performance of the developed artificial neural networks for the MDF boards is slightly better than the performance of the ANN models, which were designed for particleboards (Table 6). This could be due to the fact that the MFD have more of a homogenous structure than the prelaminated wood particleboards.…”
Section: Ann Modelingsupporting
confidence: 66%
“…By comparing the factor coefficients of Equation ( 7), one could observe that drill type (X 3 ) has a bigger influence than the drill tip angle (X 1 ) and tooth bite (X 2 ). This result is contrary to the results obtained in the case of prelaminated particleboards, where the most important factor that affects the delamination factor at inlet (Y 1 ) is the tooth bite [14]. This result is correlated with data reported in the literature; namely, the feed rate and drill tip angle play an important role on the value of delamination factor [2,6,8,9,12].…”
Section: Delamination Factor At the Inletcontrasting
confidence: 55%
See 2 more Smart Citations
“…Various artificial intelligence solutions are widely used in the wood industry in general. Monitoring operational performance [ 11 ], optimizing drilling parameters [ 12 ] and AI algorithms perform well for various complex problems. The applications of such algorithms are also growing increasingly common in the wood industry in general, especially when it comes to problems encountered during the drilling process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%